THE EFFECT OF THE EXISTENCE OF SAND MINING ON DAMAGE TO THE SETTLEMENT ENVIRONMENT IN LAJULO VILLAGE, BARRU DISTRICT, BARRU REGENCY - Nadila, Ade Rifki (UNM Geographic Journal, 2022)
The research was carried out with the objectives of: 1) knowing the description of sand mining on settlements in Lajulo village, Barru district, Barru district. 2) Knowing the description of the residential environment due to sand mining in Lajulo village, Barru district, Barru district. 3) Knowing the effect of sand mining on the residential environment in Lajulo Village, Barru District, Barru Regency. The type of research used is descriptive quantitative. The variables of this study consisted of Sand Mining (variable x) and Environmental Damage (variable y). Data collection techniques used observation, questionnaires and documentation. The data analysis technique used is descriptive statistics and inferential analysis. Based on the research, it is known that: 1) sand mining (X) in Lajulo Village, Barru District, Barru Regency is included in the "Medium" category. By using the variables of social conditions and economic conditions . 2) Based on the results of research and analysis of environmental dredging (Y) in Lajulo Village, Barru District, Barru Regency, it is included in the "High" category. By using the variables of the physical environment and biological environment.